Museum Ecologies - Christina Fredengren; Annica Ewing; Caroline Owman; Janna Holmstedt (Museum & Society)
New research highlights the importance of making more productive connections between museum work and the environment to take action and work more sustainably. This paper provides a novel entry on how to understand museum things as consisting of bundles of ecological relations. This new way of understanding how things exist provides an important method for tracing how museums impact environmental change. In our pilot study Museum Ecologies, we have worked with digital collection databases as an example to show how museum collections are interlinked with climate change and climate change transitions. The research elaborates and expands upon the museum pedagogic method, Tingenes Metode, to explore how this can be developed beyond its anthropocentric notions, using environmental humanities perspectives, and tools from a variety of thinkers within critical feminist post-human and new materialist theories. This paper investigates how museums and cultural heritages, observed, and understood as ecological agents, can guide us as we struggle to find new ways to live in the Anthropocene.